2020
DOI: 10.1210/clinem/dgaa576
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Nephrolithiasis and Hyperoxaluria in Paget Disease of Bone

Abstract: Context Nephrolithiasis (NL) and primary hyperparathyroidism (HPTH) are metabolic complications of Paget’s Disease of Bone (PDB), but recent data regarding their prevalence in PDB patients are lacking. Objectives Study 1: To compare the prevalence of primary HPTH and NL in 708 PDB patients and in 1803 controls. Study 2: To evaluate the prevalence of NL-metabolic risk factors in 97 PDB patients with NL, 219 PDB patients withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…This study showed that VF’s were common (about 36%) among those hospitalised with severe SARS Cov2 compared with the general population where the prevalence of VFs ranged from 18–26% in women and 8–20% in men. The presence of VFs in this study was a strong prognostic marker and predictor of clinical outcomes and disease severity as other well-described risk factors and co-morbidities, although the prevalence of VFs in the study population was higher than previously reported in the European general populations [ 43 , 44 ]. Furthermore, patients with VFs were more likely to require non-invasive mechanical ventilation (48.8% vs 27.4%, p = 0.02).…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…This study showed that VF’s were common (about 36%) among those hospitalised with severe SARS Cov2 compared with the general population where the prevalence of VFs ranged from 18–26% in women and 8–20% in men. The presence of VFs in this study was a strong prognostic marker and predictor of clinical outcomes and disease severity as other well-described risk factors and co-morbidities, although the prevalence of VFs in the study population was higher than previously reported in the European general populations [ 43 , 44 ]. Furthermore, patients with VFs were more likely to require non-invasive mechanical ventilation (48.8% vs 27.4%, p = 0.02).…”
Section: Methodscontrasting
confidence: 59%
“…Furthermore, patients with VFs were more likely to require non-invasive mechanical ventilation (48.8% vs 27.4%, p = 0.02). Mortality was higher in those with severe VFs (60%) compared with those with moderate or mild VFs (7% and 24%, respectively) [ 43 ]. The author speculated that impaired respiratory function and kyphosis associated with VF’s may decrease vital lung capacity and increase the risk of severe SARS Cov2 infection.…”
Section: Methodsmentioning
confidence: 99%
“…Noteworthy, a Cochrane meta-analysis did not indicate an increased risk of hypercalcemia, hypercalciuria or nephrolithiasis in patients with vitamin D deficiency treated with cholecalciferol [119]. Moreover, the correction of vitamin D deficiency with cholecalciferol in patients with Paget's disease of the bones, who are at increased risk of nephrolithiasis [120], did not cause either an increase in supersaturation indices of calcium-oxalate and calcium-phosphate salts or a rise in urinary pH and urinary excretion of urate, the major risk factors for calcium and urate nephrolithiasis, respectively [121].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…Metabolic complications of PDB include hypercalcemia, hypercalciuria, hyperoxaluria, and hyperuricemia [ 43 ]. Disturbances in calcium homeostasis can lead to kidney stone formation and nephrolithiasis (NL), the most frequent kidney complication of PDB [ 47 ]. NL has been described as a possible non-malignant metabolic complication of PDB [ 43 ].…”
Section: The Clinical Approach Illustrationmentioning
confidence: 99%
“…This association remained significant also in a model adjusted for age, sex, BMI, and eGFR [OR 2.26 95% C.I. : 1.72–2.98, p < 0.01] [ 47 ]. The rate of recurrence of NL was higher in the polyostotic group than in the monostotic group of patients with PDB.…”
Section: The Clinical Approach Illustrationmentioning
confidence: 99%